Changing geographic ranges of ticks and tick-borne pathogens: drivers, mechanisms and consequences for pathogen diversity - Ogden, Nicholas (Frontiers in Cellular and Infection Microbiology, 2013)
The geographic ranges of ticks and tick-borne pathogens are changing due to global and local environmental (including climatic) changes. In this review we explore current knowledge of the drivers for changes in the ranges of ticks and tick-borne pathogen species and strains via effects on their basic reproduction number (R0), and the mechanisms of dispersal that allow ticks and tick-borne pathogens to invade suitable environments. Using the expanding geographic distribution of the vectors and agent of Lyme disease as an example we then investigate what could be expected of the diversity of tick-borne pathogens during the process of range expansion, and compare this with what is currently being observed. Lastly we explore how historic population and range expansions and contractions could be reflected in the phylogeography of ticks and tick-borne pathogens seen in recent years, and conclude that combined study of currently changing tick and tick-borne pathogen ranges and diversity, with phylogeographic analysis, may help us better predict future patterns of invasion and diversity.